On uniform convergence Fourier series - Radzievska, Elena (My University, 2020)
In terms of the best approximations of a function in the space Lp, the condition for the existence of (ψ, β) -derivatives and uniform convergence of the Fourier series to them is found. У термінах найкращих наближень функції в просторі Lp знайдено умова існування у неї (ψ, β) - похідних і рівномірної збіжності до них рядів Фур'є.
Keywords: кафедра вищої математики імені проф. Можара В. І.; ψ, β-derivatives; uniform convergence of Fourier series; approximations of a function; Lp spaces; ψ, β-похідні; рівномірна збіжність рядів Фурьє; наближення функцій; простори Lp